Flu immunization during pregnancy: a cross-sectional study among Italian healthcare providers: Francesca Licata. (25th October 2022) - Licata, F; Angelillo, S; Della Polla, G; Pelullo, CP; Napolitano, F; Di Giuseppe, G; Romeo, M; Bianco, A
Abstract: Background: Flu vaccination during pregnancy has been proven to be effective in preventing illness and hospitalization in both pregnant women and newborns. However, flu vaccination uptake is still suboptimal. The study aimed to assess if healthcare providers (HCPs) are knowledgeable about flu vaccination recommendation during pregnancy and if they routinely recommend the vaccination. Methods: The present survey was carried out among obstetricians-gynaecologists (OBs), midwives and primary care physicians (PCPs) in the Southern part of Italy. Data were collected through an anonymous self-administered questionnaire that included professional information, knowledge, perceptions and practices on flu vaccination during pregnancy. Results: 96 participants were hitherto enrolled (36.5% OBs, 35.4% PCPs and 28.1% midwives). Among the responders, 63.5% and 66.7% knew that flu vaccination can be administrated during any trimester of pregnancy and reduces the risk of preterm birth and miscarriage, respectively. Alarmingly, more than a fifth (22.9%) of the sample believed that vaccines during pregnancy are more dangerous than safe and only 67.7% routinely recommend the flu vaccine to all women regardless of their stage in pregnancy. Among HCPs who did not recommend the flu shot, the most frequently reported reasons were that flu vaccine recommendation was outside the scope of their practice (62.5%), that women are more hesitant about vaccines during pregnancy (37.5%) and lack of time (25%). Conclusions: The preliminary results highlight alarming gaps in knowledge (e.g. immunization timing) and suboptimal routine recommendation of the flu vaccine that represents a missed opportunity. Indeed, it has been demonstrated that when women are offered vaccination, most tend to accept it. Key messages:  Unmotivated concerns about vaccine safety during pregnancy have to be addressed among HCPs to enhance flu recommendation and, subsequently, immunization coverage in pregnant women.  Strategies to disseminate evidence-based recommendations to HCPs regarding flu immunization during pregnancy have to be implemented and evaluated in order to improve public health.